The Implementation of Quizziz as Assessment for Learning in English as A Foreign Language: The Teacher’s Perspective - Sanjaya, I Agus Rudi; Suprianti, Gusti Ayu Putu; Paramartha, Anak Agung Gede Yudha (STKIP AGAMA HINDU SINGARAJA, 2023)
This research aims to (1) describe the implementation of Quizizz as an English Language Learning Assessment for Teachers at SMP 1 Nusa Penida. (2) identify the Teacher problem in implementing Quizizz as Assessment for Learning English at SMP 1 Nusa Penida. (3) investigate what EFL Teacher at SMP 1 Nusa Penida overcome the problems that they faced in implementing Quizizz as Assessment for Learning English at SMP 1 Nusa Penida. The method of this study was a descriptive qualitative. The subject of this study is one English teacher at SMPN 1 Nusa Penida. In this study concluded that the implementation of Quizizz as Assessment for Learning in English learning process in seventh grade especially about the characteristic of Assessment for Learning runs according to the theory used as a reference. The indicators used to test the problems faced are theory about the characteristic of Assessment for Learning by Tetahuhu o te Matauranga. This study also concluded that there were several strategies found that used to solve several problems faced by teachers when implementing Quizizz as Assessment for Learning in English learning process.